2015
DOI: 10.1007/s13277-015-3407-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of the multidrug resistance 1 gene MDR1 and the risk of hepatocellular carcinoma

Abstract: A possible association between multiple drug resistance 1 gene (MDR1) polymorphisms and the risk of developing hepatocellular carcinoma (HCC) is currently under debate, and evidence from various epidemiological studies has yielded controversial results. To derive a more precise estimation of the association between MDR1 polymorphisms and HCC risk, the present meta-analysis was performed. A total of 8 studies containing 11 cohorts with 4407 cases and 4436 controls were included by systematic literature search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Previous study indicated that pretreatment with PPI significantly enhanced the sensitivity of tumors [13]. Consistently, the present study indicated that PPI pantoprazole arrested the MDR leukemic K562/A02 and K562/ADM cells in S phase and The classical mechanism of MDR is related with MDR1 gene and its production P-gp [14][15][16]. As a glycoprotein with 1280 amino acids, P-gp can bind hydrophobic antitumor drugs through the hydrophobic cites and pump drugs out of cells against the concentration gradient with energy provided by ATP to decrease the intracellular drug concentration and result in resistance.…”
Section: Discussionsupporting
confidence: 88%
“…Previous study indicated that pretreatment with PPI significantly enhanced the sensitivity of tumors [13]. Consistently, the present study indicated that PPI pantoprazole arrested the MDR leukemic K562/A02 and K562/ADM cells in S phase and The classical mechanism of MDR is related with MDR1 gene and its production P-gp [14][15][16]. As a glycoprotein with 1280 amino acids, P-gp can bind hydrophobic antitumor drugs through the hydrophobic cites and pump drugs out of cells against the concentration gradient with energy provided by ATP to decrease the intracellular drug concentration and result in resistance.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies, performed in Asian populations, have investigated associations between ABCB1 polymorphisms (including rs1128503) and the risk of developing HCC. A recent meta-analysis[ 55 ] showed that polymorphic alleles of the ABCB1 gene significantly increased HCC risk. In analyses of subgroups with different types of variations, both synonymous and non-synonymous polymorphisms were associated with elevated liver cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…TSCC is the most common type of oral squamous cell carcinoma, with strong invasiveness, easy occurrence of neck lymphatic metastasis and poor outcomes . The quality of life in TSCC patients is often reduced by dysphasia, as well as difficulties in chewing and swallowing.…”
Section: Discussionmentioning
confidence: 99%